Pengaruh Kompetensi, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai (Survey Pada PT. Bank Negara Indonesia (Persero) Tbk Kantor Cabang Muara Teweh Kabupaten Barito Utara) - Memed Erwansyah; Hj Sulastini; Hereyanto Hereyanto (Universitas Lambung Mangkurat, 2018)
The purpose of this study to prove the influensce of Competence (X₁), Work Discipline (X₂) and the Working Environment (X₃) on Employee Performance (Y).Location Research Office PT. Bank Negara Indonesia (Persero)Tbk Branch Muara Teweh, North Barito, with the size a sample of 33 employees by sampling.Obtained the velue arithmetic competence variabel equal to 2,051, work discipline variabel equal to 2,202 and work environment variabel equal to 2,369 with t table equal to 2,045 and F count equal to 23,893 and F table equal to 2,934.The result of study showed that by parsial competence variable, work discipline, and work environment variable to have an effect on the signifikan to employee performance variable And oslo by simultan of employee competence variable, work discipline dan work environment to have an effect on by signifikan to employee performance variabel. Keywords : Competence, Work Discipline, Work Environment and Performance